Pengamanan Obyek Vital Nasional Di Kawasan Industri Batamindo Kota Batam - Baru Rochim (Universitas Internasional Batam, 2020)
The Objective of this research are to analyze and to criticized the implementation of Presidential Decree No. 63:2004 On National Vital Assets in Batamindo Industrial Park are well implemented. Second reason is to analyzed what barriers process were found during its implementation, and to offer the best possible solutions to it, to maximize the implementation of Presidential Decree No. 63:2004. The research were collected from interviews, observations & questioners to HR Managers in Batamindo Industrial Park. The research was done by using Juridical Sociology approach. The research result shows that juridical commitment from Batamindo Industrial Park caretaker, Internal Security and State Police in charge for this National Asset security based on Presidential Decree No. 63:2004 On National Assets were well implemented. To have a measurable result, socialization to managerial & operational level is highly needed as the above law is still brand new and less than two years. Out of this, security guards, as the front liner of this National Assets in Batamindo Industrial Park Muka Kuning to be strengthen.